Understanding cash sharing: A sustainability model - Leire San-Jose; Ana Beraza; José Luis Retolaza (International Journal of Financial Studies, 2019)
Traditionally, corporate treasury management has been strategically based on the idea of advancing collections and delaying payments, which has been regulated through the intermediation of financial entities using, for example, credit accounts. New technologies applied to the financial field facilitate direct interaction between companies and reduce the transaction costs, because they allow adjustment of the flows of needs, but high confidence is required. The current ease of access to credit does not promote the incorporation of new financial relationship systems, but the operation of these systems should be studied, since a future credit restriction, like that known in Europe at the end of the 2000s, could change the situation. The aim of this paper was to identify the factors involved in this relationship among companies and establish the main conditions for cash sharing between companies to achieve a successful financial function. The investigation is based on a Delphi analysis used to analyze the successful experiences of shared cash (Mondragon Corporation, Trocobuy, and Arboribus), the needed variables, and their context. Then, our model was created from that exploratory knowledge. Our model is called mutual cash holding and its relevance and reliability were contrasted using structural equations based on a questionnaire administered to financial managers of large- and medium-sized Spanish companies. The result generates knowledge that articulates a new collaborative tool that expands the possibilities for treasury management among companies.
Keywords: D16; G30; 330; cash management; corporate sustainability finance; trust; transparency; collaboration